Higher levels of total cholesterol/high-density lipoprotein cholesterol ratios are associated with an increased risk of suicidal behavior in children and adolescents with depressive disorders - Sun, Nana; Liu, Zhiwei; Sun, Liang; Sun, Feng; Sun, Longlong; Zhang, Jingjing; Yang, Rongchun; Yao, Gaofeng; Liu, Yun (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the prevalence of suicidal ideation (SI) and suicidal attempt (SA) in inpatients with childhood and adolescent depressive disorders and the relationship between triglyceride/high-density lipoprotein cholesterol (TG/HDL-C), total cholesterol/high-density lipoprotein cholesterol (TC/HDL-C) ratios and SI, SA.MethodsA study was conducted involving 515 pediatric patients diagnosed with depressive disorders at the Third People’s Hospital of Fuyang. This research primarily focused on gathering basic demographic and clinical data. Through employing methods such as correlation analysis and logistic regression, the study aimed to identify factors linked to SI and SA among these individuals.ResultsThe prevalence of SI and SA was 20.0% (103/515) and 9.1% (47/515). Binary logistic regression highlighted several independent predictors for SI. A notable increase in the likelihood of SI was observed with an increase in the number of hospitalizations (Odds Ratio [OR]=1.65, P=0.025), a heightened TC/HDL-C ratio (OR=1.72, P=0.002), an escalated antidepressant dosage (OR=1.02, P=0.029), and elevated HAMD scores (OR=1.04, P=0.003). For SA, critical independent associated factors identified were an increased number of hospitalizations (OR=2.71, P<0.001), a higher TC/HDL-C ratio (OR=1.69, P=0.002), and greater HAMD scores (OR=1.06, P=0.003), particularly in children and adolescents diagnosed with depressive disorders.ConclusionThese findings suggest that monitoring lipid profiles, particularly the TC/HDL-C ratio, alongside careful management of antidepressant dosages and close observation of depressive symptoms, could be crucial in mitigating suicidal risks among this vulnerable population.